The practices, knowledge, and attitudes about common hereditary cancers: survey of general practitioners in Johannesburg - Van Wyk, Chantel (My University, 2009)
ABSTRACT INTRODUCTION: Cancer is one of the most common diseases in the developed world and both genetic and environmental factors play a role in the development of cancer. About 5-10% of all cancers are due to predisposing genes. Some of the more common inherited cancer syndromes are hereditary breast and ovarian cancer (HBOC) and two colorectal cancer syndromes, familial adenomatous polyposis (FAP) and hereditary nonpolyposis colorectal cancer (HNPCC). Recognition of cancer susceptibility can allow “at risk” individuals and families to participate in cancer risk assessment, genetic testing, and various cancer prevention strategies. As the public is becoming more aware of inherited cancers, it is expected that there will be an increasing demand for genetic services and testing. For this reason more GP involvement is required to assess patients and families at risk and refer them appropriately. Since the Clinical and Counselling Section, Division of Human Genetics, National Health Laboratory Service and University of the Witwatersrand, Johannesburg is establishing a cancer genetics service it woud be of great value to assess the GPs’ practice, knowledge and attitudes with regards to cancer genetics and this was therefore the aim of this study. METHODOLOGY: A quantitative, exploratory research design was chosen and GPs in the Johannesburg area were selected as subjects. After the completion of a pilot study a research package was mailed to 196 GPs. This package was sent out twice and both times the GPs were asked to respond within 3-4 weeks. The final sample consisted of 61 GPs and the data were analysed using descriptive statistics. RESULTS: Of the 61 participants more male GPs (42, 69%) than female GPs (19, 31%) responded and there were about an equal number of GPs practicing alone (29, 48) and in a multiple practice (32, 52%). Twenty two (33%) of the GPs had never had personal experience of cancer. Practices: The GPs made use of several cancer screening procedures but obtained limited information on cancer history from their patients particularly from second degree relatives and about age of onset. Very few subjects (15, 25%) reported that they assess patients’ risk for inherited cancer susceptibility and only 22 (36%) reported that they refer patients to other facilities for risk assessment and genetic testing. Knowledge: Only 32 (52%) of the GPs were aware of genetic testing facilities and 54 (86%) reported never having received advertising material to promote genetic testing for cancer susceptibility services. They also are not aware of genetic counselling facilities but do feel patients should have genetic counselling by a genetic counselor, clinical geneticist or oncologist before genetic testing. Even though genetic testing for inherited cancer susceptibility is only available at some academic institutions, mostly on a research basis, the GPs seem to be unaware of the availability of genetic testing in South Africa for colorectal cancer genes (8, 13% and 9, 15%) but 28 (46%) knew about breast cancer genes. They were not aware of the autosomal dominant inheritance of hereditary breast cancer and the percentage of individuals with breast cancer who carry the BRCA1/2 gene nor did they know the penetrance of HNPCC genes. Attitudes: The subjects’ attitudes to genetic testing for inherited cancer susceptibility were positive although they reported that they were unaware of several general factors regarding cancer genetic testing. The GPs had limited knowledge about inherited cancers and do not take an active part in cancer genetic management. However, 53 (87%) of the GPs reported interest in learning about these services and expected to play a role in cancer genetics in the future. CONCLUSION: The findings of this study suggest that there is a need to educate GPs about the basic cancer genetic concepts so that they can identify patients at risk for an inherited cancer syndrome. They need to be informed about the genetic tests currently available for the inherited cancer syndromes, and about genetic counselling and testing facilities.
Keywords: Johannesburg; survey; inherited cancers; genetics; general practitioners; hereditary cancers